New Student Interest: Price, Promotion, and School Image in Vocational High School: Faktor-faktor yang Mempengaruhi Minat Siswa Baru: Harga, Promosi, dan Citra Sekolah dalam Sekolah Menengah Kejuruan Swasta - Dea Ayu Tisna; Mas Oetarjo (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study aims to examine the impact of price, promotion, and school image on the interest of new students at a private vocational high school in Sidoarjo, East Java. The research utilized a saturated sampling technique, encompassing all 42 new students who registered at the school. IBM SPSS V. 25 software was employed for data analysis, including classical assumption tests, multiple linear regression analysis, t-tests, multiple correlation coefficient tests, and the coefficient of determination. The findings reveal that price, promotion, and school image all significantly influence the interest of new students at the vocational high school. This study provides valuable insights for educational institutions in understanding the factors that affect new student interest, guiding their efforts to attract and retain students. Highlights: Factors influencing new student interest: Examining the impact of price, promotion, and school image on the interest of new students. School choice determinants: Analyzing the significance of these factors in shaping the decision-making process of new students. Implications for educational institutions: Providing insights for private vocational high schools in attracting and retaining new students through effective pricing strategies, promotional activities, and cultivating a positive school image. Keywords: price, promotion, school image, new student interest, private vocational high school